Flow cytometry sorting of cells infected with African swine fever virus - A. S. Pershin; I. V. Shevchenko; T. N. Komova; A. Mazloum; N. N. Vlasova; E. O. Morozova; A. S. Igolkin; K. N. Gruzdev (Ветеринария сегодня)
The African swine fever panzootic  is continuing  to spread,  and the number  of affected countries and material losses are increasing. In particular, India, Papua New Guinea, Malaysia, Greece and Bhutan joined the list of ASF infected countries in 2020–2021. The disease control is hindered  by the lack of commercially available and effective vaccines, which, in its turn, is attributable  to the insufficient knowledge of ASF pathogenesis  and immune defense against the disease. The use of attenuated virus variants enables a thorough  investigation of the factors influencing the virulence of African swine fever virus and the immune  response  to it. This involves the use of naturally attenuated virus variants, as well as of the variants attenuated by a long-term passaging of the virus in cell cultures. However, virulence heterogeneity characteristic of the ASF virus population, necessitates  the additional selection of infected cells for the virus cloning. Conventional culture-based techniques for virus particle cloning are rather time- and labour-consuming;  it is therefore appropriate  to use flow cytometry cell sorting for the selection and cloning of virus infected cells with a view of selecting  homologous  virus lineages.  The paper  presents  the results of sorting  of African green  monkey kidney cells (CV-1) and porcine bone marrow cells infected with African swine fever virus; the cells were sorted into the 96-well culture plates using a MoFlo  Astrios   EQ cell sorter in order to isolate a population of the virus originating from one infected cell. After the single cell sorting of the infected cell cultures into the 96-well plates, ASF positive cell detection  rates in the plate wells were 30% for porcine bone marrow cells and 20% for CV-1.